A STUDY ON THE IMPLEMENTATION OF ENGLISH SONGS IN TEACHING VOCABULARY MASTERY - Nurkhalizah Lembah; Konder Manurung; Mashuri Mashuri (Tadulako University, 2021)
A song is a type of teaching media that can be used to teach any subject. It can also be used to teach vocabulary because song lyrics contain a variety of vocabularies. The goals of this study are to describe the steps of the implementation of English Song in teaching vocabulary mastery and to describe how successful the implementation of English Song in teaching vocabulary mastery was. The study applied qualitative design that implemented Library Research Method. The data were collected from scientific writing on the implementation of English songs in teaching vocabulary between 2011 and 2021. The scientific writing were found from the library and internet. The data were analyzed using content analysis based on Dale (1992). The results reveal that there are five scientific writings from Widhiastuti (2012), Febria (2015), Gushendra (2017), Bahri (2018), and Sari (2019). The results of the data analyzed show that the implementation of English Song in five different studies by five different experts used different steps in implementing the procedure. One of them was followed the procedure suggested by Dale (1992) which is play the song with no preparation and no hand-outs. Three of them give the materials before the listening selection, and other researcher play the video or singing the song by the teacher. Based on second research question, the vocabulary mastery of students’ improve after the implementation of English Song in the classroom. The researcher conclude that the implementation of English Song in teaching vocabulary mastery has a positive effect because the students’ vocabulary has improved as a result of the research.